Financing in Education as a human right - Trejo Cruz, Yesenia del Carmen (2021)
Human rights in Mexico, in light of its incursion in the constitutional system in 2011, unfold their application in all normative areas, as a condition that improves the living conditions of Mexicans; including the educational sector, which at the same time is configured as an instrument that guarantees its fulfillment.  These prerogatives establish a paradigm, as a new legal order, that imposes on the authorities the duty to abide by them in their respective functions.  In this context, education as a guarantee is analyzed based on the sources of financing granted by public entities, which periodically face in their governmental competences, the determination of the budget that solves and guarantees its application in the national territory.  At the same time, it underlies the limits that are imposed on budget allocations, based on the justification of the collective interest, ratified by the Supreme Court of Justice of the Nation.  In this order of ideas, we indicate as an objective of the investigation, to specify the budgetary solvency granted to education as a Human Right.